(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Contemporary technologies of training specialists in different professions envisage mastering the skills of a 'quality user' of computer technologies. At the same time, the issues of training primary school teachers, specialists in inclusive and remedial education to use more complex multimedia systems with the need to understand programming processes have often been excluded from basic courses as an 'unnecessary' component.But considering the current trends towards distance education, the “rejuvenation” of 'advanced users' and the need to maintain a educator's reputation, the trend towards introducing such systemic courses in the training process for specialists in primary, inclusive and correctional education has become a kind of concept for professional competence. It was based on the needs of today's teachers to transfer knowledge through multimedia systems (creating interactive databases, web pages, blogs or websites, preparing and conducting WebQuests, using computer games from producers or their own development through the platforms Wordwall, Etreniki, Flippity and Scratch programmes, etc.) that became the deciding factor for introducing specific topics on their use into training courses and expanding basic programmes of computer competency. Also, the training process began to include interaction with the training audience through social media. This multi-component work to develop a «modern/advanced» teacher provides the basis not only for improving the quality of the educational process, but also for its individualization according to the needs of each participant and his/her special educational needs, allowing to change the complexity of tasks, the saturation of tasks with audiovisual information.